The Effect of Task-Oriented Basketball Training on Motor Skill-Related Fitness in Children with Developmental Coordination Disorder - Faiçal Farhat; Achraf Ammar; Nourhen Mezghani; Mohamed Moncef Kammoun; Khaled Trabelsi; Adnene Gharbi; Lassad Sallemi; Haithem Rebai; Wassim Moalla; Bouwien Smits-Engelsman (Sports)
Developmental Coordination Disorder (DCD) is one of the most prevalent neurodevelopmental disorders in childhood. DCD is classified as a motor learning deficit because it interferes with the ability to learn and automate movement skills. There is a lack of information on how these children acquire complex motor skills relevant to their daily recreational or sports activities. Evidence to guide physical trainers, educators, and health professionals to select an effective type of training to improve physical fitness for children with poor motor coordination is scarce. The purpose of this study was to analyze the effect of an 8-week task-oriented basketball training program on motor coordination and motor skill-related fitness for DCD children in the school context. Motor performance and motor skill-related fitness were evaluated before and after the intervention using the Movement Assessment Battery for Children-2 (MABC-2) and Performance and Fitness Test Battery (PERF-FIT). A total of 52 children with DCD aged 8 to 9 were invited to join the intervention. Parents of 18 children accepted for their child to participate in the training program. In the remaining children, 20 identified as the most similar based on the diagnostic criteria for DCD (DSM-5) and anthropometric features (age, BMI) and were asked to participate as the usual care group. The difference in improvement on the MABC-2 and the PERF-FIT between the two groups on the two test occasions was compared using Mann–Whitney U tests. Within-group pre-post comparison on these test items was performed using the Wilcoxon signed rank test. Significant differences in all performance scores were found in favor of the training group. Post-hoc analysis revealed that the DCD training group improved significantly on MABC-2 total and subscores (p < 0.001) and on all PERF-FIT items (p < 0.001). No significant changes were found on any of the test items in the DCD usual care group. Group-based training in a more natural environment (playing games with peers in school) might help children with DCD as an adjunct to or before individual therapy. Based on our findings, we believe it is possible to work in large groups (n = 18), led by trained physical education teachers and special educators, to lessen the impact of motor coordination and physical fitness problems in children with neurodevelopmental disorders so that they can participate more easily in active games. Results of the usual care group showed that extra instruction and practice are needed for children with DCD.